From animal baits to investors' preference: Estimating and demixing of the weight function in semiparametric models for biased samples - Ya'acov Ritov; Wolfgang Karl Härdle (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
We consider two semiparametric models for the weight function in a bias sample model. The object of our interest parametrizes the weight function, and it is either Euclidean or non Euclidean. One of the models discussed in this paper is motivated by the estimation the mixing distribution of individual utility functions in the DAX market.
Keywords: C10; C14; D01; D81; 330; Mixture distribution; Inverse problem; Risk aversion; Exponential mixture; Empirical pricing kernel; DAX; Market utility function; Nichtparametrisches Verfahren; Stichprobenverfahren; Bias; Anlageverhalten; Präferenztheorie; Risikoaversion; Theorie; Deutschland